ANALISIS FAKTOR KESULITAN BELAJAR SISWA PADA PELAJARAN BIOLOGI SECARA DARING DI SMAN 13 TAKALAR - Saparuddin (Universitas Cokroaminoto Palopo, 2022)
Learning difficulties are the inability of students to master a subject matter maximally within the allotted time due to several factors that influence it. The application of online learning in biology lessons makes students experience problems in learning. This study aims to determine what factors influence student learning difficulties during online learning in biology lessons at SMAN 13 Takalar. The research method uses a quantitative descriptive approach. The data collection technique was in the form of a student response questionnaire regarding learning difficulties in biology lessons online at SMAN 13 Takalar. The results of the descriptive analysis of the study indicate that the factors that influence students' learning difficulties in online biology lessons at SMAN 13 Takalar are health factors which are classified as moderate category, students' boredom factor is classified as moderate category, family factors are classified as low category, school factors are classified as low category, mass media factors are classified as low category and environmental factors are classified as medium category.